Bi-scale interfacial bond behaviors of CCF/PEEK composites by plasma-laser cooperatively assisted 3D printing process. (April 2020) - Luo, Meng; Tian, Xiaoyong; Shang, Junfan; Yun, Jingxin; Zhu, Weijun; Li, Dichen; Qin, Yingjie
Abstract: 3D printed continuous carbon fiber reinforced PEEK (CCF/PEEK) composites have got much attention because of their excellent mechanical, thermal and chemical performance and the formability of complex structural components. However, there are always two different weak-bond interfaces limiting the application of the composites critically, which are the poor interlayer bond and the weak interface between carbon fibers and PEEK. A plasma-laser cooperatively assisted 3D printing process was utilized to improve the bi-scale interface. After optimizing, the interlaminar shear strength can be improved from 5.78 MPa to 39.05 MPa. After analyzing the failure mode and bi-scale interfacial bond mechanism, it's found that the laser mainly improves the interlayer bond and crystallinity, while the plasma effectively improves the mechanical modulus by treating the surface of the carbon fibers chemically and physically. The work provides a really novel idea for developing the 3D printed CCF/PEEK composites for further application in aerospace and automotive industries.